PRETEST AND POSTTEST TECHNIQUE TO CONTROL STUDENTS MASTERY IN ONLINE LEARNING OF ENGLISH FOR COMMUNICATION COURSES AT VOCATIONAL STUDIES OF IPB UNIVERSITY - Harries Marithasari; Irma G Barus; Ira Resmayasari; Bayu Suriaatmaja Suwanda (English Education Study Program STKIP PGRI Pacitan, 2023)
Abstract The purpose of this study was to determine the effect of the pretest and posttest on learning English, the English for Communication course at the Vocational School of IPB University. The methodology used is a case study. This type of research is quantitative research. Data collection was carried out by conducting tests and interviews. The subjects of this research were students of the Digital Communication and Media Study Program at the Vocational School of IPB University, totaling 300 students. From the results of this study, it shows that there was an increase in the value of the pretest and posttest. The average pretest score is 61, while the average posttest score is 80. From this process, it is known that the pretest can be used as a learning control tool. Lecturers can see that the learning techniques used can increase students' understanding of English. In addition, from the interview process, it is known that the pretest and posttest can be used by lecturers to find out students who have weak abilities and students who have high abilities.